BUSINESS ECOSYSTEM OF COMMERCIAL BANKS AND ITS ORGANIZATION PROCESSES - Shoymardonov Orziqul Jura ugli (American Journals, 2023)
This article talks about ways to improve the efficiency of banking services based on the introduction of a business ecosystem in the commercial banks of our country, the essence of the banking business ecosystem, the history of development, and the prospects for improving the advantages of the business ecosystem in commercial banks. In particular, the article presents the existing problems in increasing the efficiency of the business ecosystem in commercial banks based on the introduction of innovations, as well as the author's recommended approaches and suggestions for their elimination.
Keywords: Commercial banking, innovation, digital business, ecosystem, efficiency, innovative services, new types of services, banking business ecosystems.